Guide for the nondestructive examination of welds (American Welding Society, 2016)
"This guide acquaints the user with the nondestructive examination methods commonly used to examine weldments. The standard also addresses which method best detects various types of discontinuities. The methods included are visual, liquid, penetrant, magnetic particle, radiographic, ultrasonic, electromagnetic (eddy current), and leak testing."
"AWS B1.10M/B1.10:2016."
"Approved by the American National Standards Institute, August 29, 2016."
"Supersedes AWS B1.10M/B1.10:2009."
Keywords: Welded joints -- Testing.; Nondestructive testing.; elektronické knihy; electronic books